2021
DOI: 10.3390/su13041958
|View full text |Cite
|
Sign up to set email alerts
|

Trade Openness and CO2 Emissions: The Heterogeneous and Mediating Effects for the Belt and Road Countries

Abstract: To investigate whether increasing trade openness results in more severe environmental problems, this study investigates the impact of trade openness on carbon dioxide (CO2) emissions using panel data from 64 countries along the Belt and Road from 2001–2019. Fully considering the potential heterogeneity, the panel quantile regression approach is utilized. Moreover, this study explores the three major mediating effects of the process, namely the energy-substitution effect, economic effect, and technology effect.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(38 citation statements)
references
References 48 publications
4
22
0
Order By: Relevance
“…In addition, there is consensus in the research community that increased fossil fuel consumption is coupled with increased CO 2 emissions [31,43], which this study confirms as well. Finally, this study revealed that increased trade openness is associated with reduction in CO 2 emissions, which agrees with the work by Chen et al [25] on data from G20 countries and by Dogan and Turkekul [31] on USA, and disagrees with another work on 64 countries [44]. Our interpretation to this variation is that trade openness impact on CO 2 emissions is related to the nature of goods and services being imported and exported and their impact on the environment.…”
Section: Discussionsupporting
confidence: 81%
“…In addition, there is consensus in the research community that increased fossil fuel consumption is coupled with increased CO 2 emissions [31,43], which this study confirms as well. Finally, this study revealed that increased trade openness is associated with reduction in CO 2 emissions, which agrees with the work by Chen et al [25] on data from G20 countries and by Dogan and Turkekul [31] on USA, and disagrees with another work on 64 countries [44]. Our interpretation to this variation is that trade openness impact on CO 2 emissions is related to the nature of goods and services being imported and exported and their impact on the environment.…”
Section: Discussionsupporting
confidence: 81%
“…These sources are either aggregated economic figures (de-facto measures) or evaluations of economic transparency's structural basis, i.e., lawfully defined obstacles to exchange and financial transactions. Addressing economic openness in literature, two lines of the study available are one group of researchers have considered total trade as a percentage of GDP as a measure of EO, see Fujii ( 2019 ) and Chen et al ( 2021 ), and simultaneously another line of study has been considering FDI inflows as a measured of EO, see Steiner and Saadma ( 2016 ), Baltagi et al ( 2009 ). Furthermore, financial openness is classified according to three regimes (closed, neutral, or open) based on the KAOPEN financial openness indicator of Chinn and Ito ( 2008 ).…”
Section: Data and Methodology Of The Studymentioning
confidence: 99%
“…Other studies including gross capital formation Zhang et al, 2021). However, studies on the relationship between energy consumption, economic growth, and environmental degradation/CO2 emissions with the inclusion of gross capital formation and trade openness simultaneously are lacking in the existing literature and needs to receive more attention in empirical analysis in the future (for example, Chen et al, 2021;Ling et al, 2015;Ekundayo Peter Mesagan & Nwachukwu, 2018;Rauf et al, 2018;Soytas et al, 2007). One corresponding study by Rauf et al (2018) found that energy consumption, economic growth, and gross capital formation positively influence CO2 emissions, while trade openness and CO2 emissions are negatively connected by applying fully modified ordinary least squares (FMOLS) and dynamic ordinary least squares (DOLS) data from 47 of Belt and Road Initiative (BRI) countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is limited literature on the relationship between energy consumption, economic growth, and environmental degradation/CO2 emissions with the inclusion of gross capital formation and trade openness simultaneously (Chen et al, 2021;Ling et al, 2015;Ekundayo Peter Mesagan & Nwachukwu, 2018;Rauf et al, 2018).…”
Section: Introductionmentioning
confidence: 99%